Perancangan Dan Implementasi Sistem Pengendalian Internal dan Pencatatan Akuntansi Dengan Teknologi Web-Based Pada Sufins Coffee - Yefta Christian; Michael Michael (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This article discusses the design, development and implementation of a simple web-based internal control system and accounting records for MSMEs (Micro, Small, and Medium Enterprises). One of the problems which is commonly occur to MSMEs is that they do not have clear cash flows of the enterprise, there is also no financial information report / financial statement that can be used as a guide in making business decisions. MSMEs or the subject who experience the same problem in this study is Sufins Coffee, a business running in the field of coffee shop. The method used in this study is by observation, interviews, and documentation. The implementation of the web-based Accounting Information System (AIS) made by the author shows a very pleasing result. Reports of financial information generated by the new system can assist the owner in making decisions.